Identifikasi Prioritas Perbaikan pada Kualitas Produk Es Kopi Susu di Kovfee-Bali dengan Metode Quality Function Deployment (QFD) - Alfiana, Fitria; Hartiati, Amna; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 4 (2020): Desember, 2020)
The increasing competition of coffee shop makes entrepreneurs keep on improving the quality of their product in order to satisfy the consumers’ desire and need. One of the coffee shops in Denpasar named Kovfee with its flagship product that is milk coffee has not yet measured the consumer satisfaction with their iced milk coffee products. This study discusses the product attributes that are considered important by consumers, measures the level of consumer interest in the quality of coffee products, as well as the level of consumer satisfaction with the quality of milk coffee products in Kovfee coffee shop. The method used is the Quality Function Dep loyment (QFD) method. The research data were obtained from 91 survey respondents. The results of the questionnaire validity test of interest and satisfaction showed that there are 7 products attributes which are considered as important by consumers. The results of the reliability test calculations from the questionnaire of interests (0.715) and satisfaction (0.688) can be considered reliable. The highest value of the consumer interest is the taste attribute (3.92) which showed that the taste attribute is the most important need and desire for consumers. The lowest value of the customer satisfaction is the aftertaste attribute (2.76) with the highest IR (1.45) that indicates Kovfee coffee shop needs to provide and improve product quality in the aftertaste attribute. Keywords: iced milk coffee, product quality, customer satisfaction, quality function deployment (QFD)